Oral health‐related quality of life: pre‐ and post‐dental implant treatment. (13th May 2014) - Patel, N.; Vijayanarayanan, R.P.; Pachter, D.; Coulthard, P.
Abstract Aim Oral health changes, such as tooth loss can have a profound effect on a patient's quality of life. The partial and fully edentulous condition has negative impacts on ability to chew, speech and appearance. Dental implants support either a fixed or removable prosthesis and can provide a significant benefit to partially or fully edentulous patients. This study evaluates changes in oral health quality of life in patients receiving dental implant treatment. Materials and methods One hundred fifty patients attending a primary care dental practice specialising in dental implant treatment were given an Oral Health Impact Profile (OHIP) questionnaire to complete before their implant treatment and 6 months post‐operatively. Results One hundred seven patients successfully completed the study. Results of the analysis demonstrate statistically significant decreases in frequency of oral health problems post treatment. For every OHIP statement, the t‐test revealed a statistically significant improvement in oral health quality of life (P < 0.001). Conclusion Dental implant therapy has a positive effect on oral health quality of life as determined by the OHIP. Long term follow up is required to provide an understanding of continuing benefits from dental implant therapy.